Adjuvant Radiotherapy Improved Survival in Stage I to II Low-Grade Endometrial Stromal Sarcoma: A Retrospective Study of 152 Cases - Wang, Wenhui; Sun, Shuai; Miao, Zheng; Hou, Xiaorong; Zhang, Fuquan; Hu, Ke (Frontiers in Oncology, 2021)
Objective Low-grade endometrial stromal sarcoma (LG-ESS) is a rare gynecological tumor. For resected early-stage ESS patients, whether adjuvant radiotherapy benefits survival remains controversial. This study aimed to explore the role of adjuvant radiotherapy in stage I to II LG-ESS. Methods This article retrospectively reviewed stage I to II LG-ESS patients in our center from Jan. 1998 to Feb. 2018. All patients underwent total hysterectomy. Postoperative radiotherapy was administrated according to clinical and pathological characteristics. Results A total of 152 patients with stage I to II resected LG-ESS were included in the analysis. Forty patients received adjuvant radiotherapy (RT group), while 112 patients did not receive adjuvant radiotherapy (no RT group). The two groups were comparable in baseline characteristics, except the proportion of stage II patients in the RT group was higher (32.5% vs. 11.6%, p=0.003). For all patients, median overall survival was not reached. The median disease-free survival (DFS) was 144 months. Radiotherapy was associated with significantly improved DFS (92 months vs. not reached, p=0.008) and pelvic failure-free survival (PFFS) (92 months vs. not reached, p=0.004). Subgroup analysis demonstrated that among patients with stage IB to IIB disease, RT benefited survival most. Regarding the failure pattern, adjuvant radiotherapy significantly reduced the pelvic recurrence rate(10.0%, 4/40 vs. 28.6%, 32/112, p=0.018). There was no radiotherapy-induced grade 4 to 5 toxicity. Conclusion For patients with stage I to II LG-ESS, adjuvant radiotherapy showed significant improvement in DFS and PFFS, especially in patients with stage IB to IIB disease with tolerable adverse effects.